First record of the sea anemone Anthopleura nigrescens (Cnidaria: Actiniaria: Actiniidae) on the Pacific coast of Central America - Acuña, F.H. (2012)
We report the first record of the sea anemone Anthopleura nigrescens on the Pacific coast of Central America. Five specimens from Mata Limón (Costa Rica) were collected from rocks of a man-made breakwater at sub-tidal level. Images of live specimens are presented. A map with its worldwide distribution is included and we concluded that this actiniarian can be considered widely distributed in the Indo-Pacific.